Multi-Scale Reliability and Serviceability Assessment of in-Service Long-Span Bridges. - Noori, Mohammed (Momentum Press, 2018)
A large number of long-span bridges are under construction or have been constructed all over the world. The steady increase in traffic volume and gross vehicle weight has caused a threat to the serviceability or even safety of in-service bridges. Therefore, ensuring the safety and serviceability of these bridges has become a growing concern. In particular, long-span suspension bridges support heavy traffic volumes and experience considerable wind loads on the bridge deck on a regular basis. Excessive dynamic responses may cause large deformation and undesirable vibration of the stiffening girders. In practice, a bridge suffers from multiple types of loadings in the life cycle. In this book, a multiscale reliability method is presented for the safety assessment of long-span bridges. The multiscale failure condition of stiffness girders is the first-passage criteria for the large-scale model and the fatigue damage criteria for the small-scale model. It is the objective of this book to provide a more in-depth understanding of the vehicle-bridge interaction from the random vibration perspective. This book is suitable for adoption as a text book or a reference book in an advanced structural reliability analysis course. Furthermore, this book also provides a theoretical foundation for better understanding of the safety assessment, operation management, maintenance and reinforcement for long-span bridges and motivates further research and development for more advanced reliability and serviceability assessment techniques for long-span bridges.